Penanganan Cedera Ringan dalam Olahraga di Puskesmas Boawae: Studi Observasi dan Wawancara Tenaga Kesehatan - Moses Jefrianto Hamin; Alfaris Rae; Robertus Lili Bile (STIKes Ibnu Sina Ajibarang, 2026)
Injuries, supported by continuous education, plays an essential role in preventing further injury and Sports injuries are common occurrences in physical activities, with minor injuries being the most frequently experienced by athletes, students, and the general community. Improper initial management of minor sports injuries may lead to more severe conditions and prolonged recovery periods. This study aimed to describe the management of minor sports injuries at Boawae Public Health Center based on observation and interviews with healthcare professionals. A descriptive qualitative method was employed through direct observation and structured interviews with a general practitioner and a nurse at Boawae Public Health Center. The results indicated that the most common minor sports injuries treated were contusions, mild sprains, muscle cramps, and muscle soreness. The initial management applied by healthcare providers was based on the RICE principle (Rest, Ice, Compression, and Elevation), accompanied by injury assessment before and after treatment. In addition, patients were provided with education regarding proper injury management and injury prevention. It can be concluded that appropriate early management of minor sports ensuring safe and sustainable participation in sports activities.